The Musculoskeletal Complaints Based on Work Position inWoven Bamboo Craftsmen - Sriagustini, Isyeu; Rosmiati, Tita; Fajri, Subhan (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: Musculoskeletal disorders in Indonesia require attention due to their high prevalence. Woven bamboo craft production involves unnatural body postures at every stage, leading to potential injuries. Assessing musculoskeletal complaints can provide valuable data for ergonomic risk assessment. This study aims to analyze such complaints based on the working positions of bamboo weavers. Methods: This research is descriptive. The population in this study was all woven bamboo craftsmen with a total of 430 people. The total sample was 86 craftsmen from 20% of the population for descriptive research. The variables studied included work position and musculoskeletal complaints. Data collection was done by observation and survey. Data were analyzed descriptively by displaying the calculation results of the risk level of work positions and the risk level of musculoskeletal complaints. Results: Most of the work positions of craftsmen are in the medium-risk category (54.7%). The working position of the craftsmen who have very high-risk category is at the stage of making woven bamboo and finishing. The highest level of discharge risk is in the low complaint category (60.5%), and the high category of musculoskeletal complaints is at the stage of making the woven. Conclusion: The working position of the woven bamboo craftsmen is directly proportional to the complaints they feel. Intervention is needed to reduce the risk of injury and reduce musculoskeletal complaints felt by workers, especially in workers with very high-risk working positions.